Trust the messenger? The role of AI transparency in policy research communication - Keenan, Michael; Koo, Jawoo; Mwangi, Christine Wamuyu; Karachiwalla, Naureen; Breisinger, Clemens; Kim, MinAh (CGIAR System Organization, 2024)
A key objective of research is to ensure that audiences—including scientists, policymakers, and lay readers—find it valuable and apply it effectively.